In vitro flow and optical coherence tomography comparison of two bailout techniques after failed provisional stenting for bifurcation percutaneous coronary interventions. Issue 1 (23rd October 2018) - Adjedj, Julien; Picard, Fabien; Mogi, Satoshi; Iwasaki, Kiyotaka; Aoumeur, Hamid; Alansari, Omar; Agudze, Edem; Wijns, William; Varenne, Olivier
Abstract: Objectives: To evaluate, in vitro, SB stenting techniques after failed provisional stenting. We aimed to compare flows and stent strut apposition of T and protrusion (TAP) versus Reversed String (RS) techniques using a flow simulator, optical coherence tomography (OCT) using silicon bifurcation phantoms with different bifurcation angulations. Background: While bifurcation coronary artery stenoses are preferably treated with provisional T‐stenting strategy, the preferred bailout two stents technique to treat the side branch remains unclear. Methods and results: Eleven 30°‐angle and ten 60°‐angle bifurcation phantoms were used. After performing provisional stenting, TAP and RS techniques were compared in six phantoms with 30° and five with 60° angles. Flow measurement was performed using absolute coronary flow and particle image velocimetry techniques. Strut apposition was evaluated using OCT. Flow analyses showed that disturbed flow regions were observed in the vicinity of floating struts protruded into the lumen both regardless of TAP and RS techniques. OCT analysis showed a higher proportion of floating struts protruding into the main branch with TAP compared to RS, respectively (13% vs. 1%; P  <0.001) in both angles. Conclusions: RS reduces the proportion of floating struts protruding into the main branch compared to TAP, at comparable flow rates. Clinical studies are needed to evaluate feasibility and potential clinical benefit of this technique.